ln(9x)+ln(4x)=5

Simple and best practice solution for ln(9x)+ln(4x)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(9x)+ln(4x)=5 equation:


Simplifying
ln(9x) + ln(4x) = 5

Remove parenthesis around (9x)
ln * 9x + ln(4x) = 5

Reorder the terms for easier multiplication:
9ln * x + ln(4x) = 5

Multiply ln * x
9lnx + ln(4x) = 5

Remove parenthesis around (4x)
9lnx + ln * 4x = 5

Reorder the terms for easier multiplication:
9lnx + 4ln * x = 5

Multiply ln * x
9lnx + 4lnx = 5

Combine like terms: 9lnx + 4lnx = 13lnx
13lnx = 5

Solving
13lnx = 5

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Divide each side by '13nx'.
l = 0.3846153846n-1x-1

Simplifying
l = 0.3846153846n-1x-1

See similar equations:

| 67.3=3.2q | | 188=4x+5(2x+4) | | y=3/2x-4/9 | | 4x-15x=66 | | 160=3x+7(4x-17) | | 3(3x+5)=36 | | 6x+2(6x-7)=76 | | 3a-2=5a | | (3x^2)+4=-5x+5 | | -10=6x+2(-x+13) | | 4m^2+17m+15=0 | | 32y^5+4y^3=0 | | (3x^2-4x)(2x^3+3x-1)=0 | | 2x-2(7x-2)=64 | | -(x-7)=5+2(x-1) | | 18m+5=13m+5 | | 1.08(1.21)(8-x)=10 | | x^2+4-9=0 | | 18c+7=6c-77 | | a+5=-24 | | ln(2x+2)=2.5 | | 7x+4(4x-14)=59 | | 5b=4b-9 | | 110=5x+2(-7+10) | | 12(v+4)-4v=4(2v+4)-22 | | -p/3=4 | | 2sin^2x+sinx+1=0 | | b=4b-9 | | Y=1/2(x-4)^2-2 | | 4sin^2(x)=2cos(x) | | (cos(x)cot(x))/(1-sinx)=3 | | cosxcotx/1-sinx=3 |

Equations solver categories